GLOBAL EXISTENCE OF SOLUTIONS FOR THE DEGENERATE WAVE EQUATIONS OF KIRCHOFF TYPE WITH NONLINEAR DISSIPATIVE TERM OF VARIABLE COEFFICIENT - Cabanillas Lapa, Eugenio (2001)
In this paper we investigate the global existence and decay of solutions to a degenerate wave equations with nonlinear dissipative term of variable coefficient.